Experimental quantum forgery of quantum optical money - Karol Bartkiewicz (Nature Portfolio, 2017)
Quantum money could protect currency against cryptographic attacks Traditional cash is being gradually replaced by digital payments and transactions with digital currency, such as bitcoin. Digital transactions are currently protected by cryptographic protocols. However, these protocols are potentially susceptible to attacks using quantum factoring algorithm. If quantum factoring is implemented on quantum computers, the resulting breach of security could make today’s digital currency obsolete. It is possible, however, to replace classical digital money with so-called quantum money, i.e., sequences of quantum bits copy-protected by their quantum nature. This paper reports on the experimental quantum optical implementation of a quantum money protocol, which was experimentally tested regarding its resistance to quantum counterfeiting based on the best physically-possible copying of individual unknown quantum bits.